(untitled) (Journal of the College of Basic Education, 2023)
In Section One, a brief account is made to describe how a semantic theory explains and shows the interpretative ability of speakers. Any lexical item in a given sentence is supplied with more senses, by a dictionary, than it can bear. The task of the projection rules is to select the most suitable sense of each item in that sentence. The semantic components discussed according to the phonological and semantic representation of sentence which is the basic concern of Section Two, are associated with a linguistic description of a natural language proposed the specification of the interconnections between the three components: syntax, phonology and semantics to be of mutual dependency. Section Three advocates another split from the Standard Theory which is called Generative Semantics: a theory developed by Lackoff, McCawley, Ross and others has found its way since 1968 as a strong opponent to the Extended Theory. We also, in Section Four discuss the semantic acceptability in linguistics through drawing a distinction between grammaticality (a property belonging to a competence) and acceptability (a property identical in performance).